Evaluation of the sustainability ofthe waterdesalination process inthesemiarid potiguar: Studyof the Caatinga GrandeCommunity - Pinheiro, Lidiane Gomes; Ferreira, Douglisnilson Morais; Silva, Fernanda Lourenço; Medeiros, Josimar Araújo; Medeiros, Luciana Castro; Peixe, Paula Dorti; Moreira, Sueli Aparecida (Sociedade & Natureza, 2018)
Although groundwater is an alternative to human supply, it often presents itself unfit for consumption due to the high indices of dissolved salts. Thus, water treatment by reverse osmosis appears as an alternative to obtaining drinking water. The objective of this studywas to evaluate the environmental, economic and social sustainability of the process of desalination of groundwater in theCaatingaGrande community in São José do Seridó/RN. A community study was carried out with technical visits to seize data on the system, to verify the environmental perception of the residents and to carry out collections of the main sources of water available in the community water treatment system.By means of the results it was found that the system is socially sustainable, since itfavored the coexistence of the population with the local reality.. The economic and environmental sustainability, despite the high costs of maintaining and producing tailings, demandsinterventions of the order of public policies and advanced research to benefit the communityin order to make the system self-sustaining.. It is concluded that, forthe development of rural communities, the groundwater desalinization systemis a viable strategy when employing post-treatment techniques and financial resources in a sustainable manner.